2018
DOI: 10.1002/celc.201800339
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Oxide‐Loaded Superparamagnetic Iron Oxide Nanoparticles for Ultrasensitive Electrocatalytic Detection of MicroRNA

Abstract: We report the electrocatalytic activity of a new class of superparamagnetic nanoparticles, graphene‐oxide‐loaded iron oxide (GO/IO hybrid material), towards the reduction of ruthenium hexaammine(III) chloride (Ru(NH3)6]3+, RuHex). Leveraging the electrocatalytic activity of the GO/IO hybrid material and the signal enhancement capacity of [Ru(NH3)6]3+/[Fe(CN)6]3− in an electrocatalytic cycle, an ultrasensitive and specific electrochemical sensor was developed for the detection of cancer‐related microRNA (miRNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The catalytic reaction typically generates a blue‐colored charge transfer complex (diamine), which in turn becomes yellow upon the addition of acid. This reaction has been widely used to design sensitive biosensors for detecting hydrogen peroxide, glucose, cells, and disease‐specific biomolecules ,,,. Recently, we have reported the synthesis and peroxidase mimetic activity of gold‐loaded nanoporous iron oxide materials for colorimetric and electrochemical detection of cancer biomarker, p53 autoantibody .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic reaction typically generates a blue‐colored charge transfer complex (diamine), which in turn becomes yellow upon the addition of acid. This reaction has been widely used to design sensitive biosensors for detecting hydrogen peroxide, glucose, cells, and disease‐specific biomolecules ,,,. Recently, we have reported the synthesis and peroxidase mimetic activity of gold‐loaded nanoporous iron oxide materials for colorimetric and electrochemical detection of cancer biomarker, p53 autoantibody .…”
Section: Resultsmentioning
confidence: 99%
“…Among various nanostructures, iron oxides (particularly maghemite, γ‐Fe 2 O 3 and hematite, α‐Fe 2 O 3 ) have been widely used for environmental and biomedical applications, such as magnetic isolation, bio‐separation, and purification, due to their excellent magnetic properties, good biocompatibility, low‐cost preparation, easy biofunctionalization and high‐stability . In our recent reports, we have demonstrated the excellent electrocatalytic properties of mesoporous iron oxide materials for detecting circulating tumor RNA and desease‐specific microRNA (miRNA) . These materials were employed to modify the conventional electrode surface, capture target sequence onto transduction surface and catalyze the electrochemical signals to achieve ultrasensitive enzyme‐free miRNA sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In electrochemical sensing and biosensing graphene materials have been widely used as platforms for the immobilization of various receptors (see illustration from Figure A) . One of the greatest challenges that are faced when developing a biosensor include the formation of a stable and specific layer of the biorecognition element.…”
Section: Graphene For Electrochemical Biosensing: Challenges and Solumentioning
confidence: 99%
“…An increasing number of reports have indicated that functional nanomaterials can be an effective alternative strategy for enhancing the sensitivity and specificity of biosensors due to their electrocatalytic activity [93], such as metal oxide nanomaterials [94], platinum nanoparticle (PtNPs) [95] and magnetic nanoparticles [96]. For instance, a miRNA sensing scheme was developed based on the electrocatalytic properties of PtNPs and DSNSA, in which PtNPs are modified with complementary ssDNA probes at first, then with the progress of DSNSA, some of the PtNPs surfaces are exposed, reactivating the PtNPs-based electrocatalytic amplification [95].…”
Section: Additional Micro- and Nano-materialsmentioning
confidence: 99%